Population structure and genetic diversity of a coffee germplasm collection in China revealed by RAD-seq - Jiang, Xinlei; Liu, Cheng; Ma, Guanrun; Zhao, Mingzhu; Li, Meifang; Chen, Tianming; Zhao, Pingxiang; Wang, Jingmin; Luo, Qin; Guo, Tieying; Su, Linlin; Zhang, Zhirun; et al. (Frontiers in Plant Science, 2025)
Coffee (Coffea spp.), a globally important crop, faces challenges in germplasm conservation due to habitat loss, climate change, and limited genetic diversity validation. This study aimed to evaluate the genetic representativeness of a coffee germplasm collection (CCGC, n=185) spanning major global varieties and wild relatives using re-striction-site associated DNA sequencing (RAD-seq). We performed genome-wide SNP profiling (37,729 loci), population structure analysis (STRUCTURE, PCA), and selection sweep detection (π) to assess genetic diversity, differentiation, and functional gene coverage. Results demonstrated that CCGC captured 98% of known disease-resistance loci (e.g., SH3, RppM) and exhibited high genetic diversity (π=0.1456, He=0.3014). Population structure analysis (K=3) identified three genetically distinct subgroups, among which Group 2 exhibited the highest diversity (He=0.3014, comparable to global coffee genetic resources) and encompassed all known Hemileia vastatrix resistance loci. The SNP density (7.5× higher than 5K SNP arrays) enabled precise identification of 47 selective sweep regions linked to domestication and adaptation. These findings validate CCGC as a genomically representative resource for coffee breeding and conservation. This work advances coffee genetic research by bridging resource preservation with molecular breeding strategies to address climate resilience and sustainable production.